Impact of alprazolam in allostatic load and neurocognition of patients with anxiety disorders and chronic stress (GEMA): observational study protocol. Issue 7 (14th July 2015) - Soria, Carlos A; Remedi, Carolina; Núñez, Daniel A; D'Alessio, Luciana; Roldán, Emilio J A
Abstract : Introduction: The allostatic load model explains the additive effects of multiple biological processes that accelerate pathophysiology related to stress, particularly in the central nervous system. Stress-related mental conditions such as anxiety disorders and neuroticism (a well-known stress vulnerability factor), have been linked to disturbances of hypothalamo–pituitary–adrenal with cognitive implications. Nevertheless, there are controversial results in the literature and there is a need to determine the impact of the psychopharmacological treatment on allostatic load parameters and in cognitive functions. Gador study of Estres Modulation by Alprazolam, aims to determine the impact of medication on neurobiochemical variables related to chronic stress, metabolic syndrome, neurocognition and quality of life in patients with anxiety, allostatic load and neuroticism. Methods/analysis: In this observational prospective phase IV study, highly sympthomatic patients with anxiety disorders (six or more points in the Hamilton-A scale), neuroticism (more than 18 points in the Neo five personality factor inventory (NEO-FFI) scale), an allostatic load (three positive clinical or biochemical items at Crimmins and Seeman criteria) will be included. Clinical variables of anxiety, neuroticism, allostatic load, neurobiochemical studies, neurocognition and quality of life will be determined prior and periodically (1, 2, 4, 8, and 12 weeks) after treatment (on demand of alprazolam from 0.75 mg/day to 3.0 mg/day). A sample of n=55/182 patients will be considered enough to detect variables higher than 25% (pretreatment vs post-treatment or significant correlations) with a 1-ß power of 0–80. t Test and/or non-parametric test, and Pearson's test for correlation analysis will be determined. Ethics and dissemination: This study protocol was approved by an Independent Ethics Committee of FEFyM (Foundation for Pharmacological Studies and Drugs, Buenos Aires) and by regulatory authorities of Argentina (ANMAT, Dossier # 61 409–8 of 20 April 2009), following the law of Habeas Data and psychotherapeutic drug control. Trial registration number: GEMA 20811.